2018
DOI: 10.1002/1878-0261.12356
|View full text |Cite
|
Sign up to set email alerts
|

S100A10, a novel biomarker in pancreatic ductal adenocarcinoma

Abstract: Pancreatic cancer is arguably the deadliest cancer type. The efficacy of current therapies is often hindered by the inability to predict patient outcome. As such, the development of tools for early detection and risk prediction is key for improving outcome and quality of life. Here, we introduce the plasminogen receptor S100A10 as a novel predictive biomarker and a driver of pancreatic tumor growth and invasion. We demonstrated that S100A10 mRNA and protein are overexpressed in human pancreatic tumors compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 53 publications
2
63
3
Order By: Relevance
“…Our result is in agreement with a previous study, which showed that PDAC patients survival was associated with hypermethylation of several individual genes including SST (HR = 1.63, P = 0.03) (Henriksen et al , 2016). In this regard, Bydoun et al (2018) reported a S100A10 mRNA and methylation status as predictive of pancreatic cancer survival where hypermethylation and lower expression were correlated with better survival. In another study, DNA methylation and altered expression of MET and ITGA2 was associated with patient survival and patients with coordinated hypomethylation and high expression of MET and ITGA2 strongly correlated with poor outcome ( P ‐value = 0.007 and 0.040, respectively) (Nones et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our result is in agreement with a previous study, which showed that PDAC patients survival was associated with hypermethylation of several individual genes including SST (HR = 1.63, P = 0.03) (Henriksen et al , 2016). In this regard, Bydoun et al (2018) reported a S100A10 mRNA and methylation status as predictive of pancreatic cancer survival where hypermethylation and lower expression were correlated with better survival. In another study, DNA methylation and altered expression of MET and ITGA2 was associated with patient survival and patients with coordinated hypomethylation and high expression of MET and ITGA2 strongly correlated with poor outcome ( P ‐value = 0.007 and 0.040, respectively) (Nones et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…High S100A10 expression in gall bladder carcinoma is shown to be associated with poor prognosis . Overexpression of S100A10 is also associated with poor prognosis in lung adenocarcinoma and pancreatic ductal adenocarcinoma . For lung squamous cell carcinoma, membranous immunopositivity was found (Fig.…”
Section: The Prognostic Value Of S100a10 For Cancermentioning
confidence: 88%
“…reported that the growth of Panc‐1, S100A10 depleted, in NOD/SCIS mice was hindered showing significant reduction in expression of VEGF and cyclin D1, compared to the scramble control. However, it should be noted that S100A10‐depleted panc‐1 cells have similar proliferation rates compared to the control in vitro . It still remains controversial and unclear whether the reduced tumor growth is plasminogen‐dependent or ‐independent.…”
Section: S100a10 Functions In Therapeutic Burdenmentioning
confidence: 97%
“…P11, present on the extracellular surface, is complexed with its binding partner annexin A2 (p36). We have reported that p11 regulates plasminogen activation on the cell surface of many cancer cells including fibrosarcoma, colorectal, lung and pancreatic cells (8,(11)(12)(13)(14)(15)(16). We have also reported that p11 regulates the plasmin production of stromal cells including macrophages and endothelial cells (17)(18)(19) and that p11-dependent plasmin generation is necessary for macrophage infiltration to the site of inflammation in subcutaneous tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown correlations between p11 gene expression and poor prognosis and overall survival in lung (20)(21)(22), colorectal, ovarian, kidney, gastric cancers, anaplastic thyroid carcinoma, melanoma and acute lymphoblastic leukemia (reviewed in (12)), and pancreatic ductal adenocarcinoma (PDAC) (16). P11 is upregulated in basal-type breast cancer (23) and during the process of intravasation and epithelial mesenchymal transition (24).…”
Section: Introductionmentioning
confidence: 99%